Challenges and needs in experimental therapies for multiple sclerosis. Issue 3 (June 2018) - Lutterotti, Andreas
Abstract : Purpose of review: Despite dramatic advances in the treatment of people with multiple sclerosis over the last decade, several unmet medical needs still remain and should be approached with new compounds in experimental clinical trials. The prerequisites for successful clinical trials in multiple sclerosis have changed considerably over time and activities have started to improve clinical development of new drugs in several aspects including trial designs, patient selection and outcome parameters. This review will address some of the challenges in early experimental trials in multiple sclerosis and recent approaches in the field. Recent findings: Highly intensive treatment regimens like autologous hematopoietic stem cell transplantation provide evidence for sustained long-term treatment effects in multiple sclerosis patients. Several different approaches towards neuroprotection and remyelination have entered the clinical phase and demonstrated that stabilization, even improvement of disability is achievable in short-term studies. Summary: New therapeutic strategies have entered the clinic with the prospects of long-term efficacy and enduring effects on disability progression.